Neurological Manifestations in Critically Ill Patients With COVID-19: A Retrospective Study - Fan, Siyuan; Xiao, Meng; Han, Fei; Xia, Peng; Bai, Xiaoyin; Chen, Huan; Zhang, Hongmin; Ding, Xin; Zhao, Hua; Zhao, Jing; Sun, Xuefeng; Jiang, Wei; et al. (Frontiers in Neurology, 2020)
Background: The complications of coronavirus disease 2019 (COVID-19) involved multiple organs or systems, especially in critically ill patients. We aim to investigate the neurological complications in critically ill patients with COVID-19. Methods: This retrospective single-center case series analyzed critically ill patients with COVID-19 at the intensive care unit of Tongji Hospital, Wuhan, China from February 5 to April 2, 2020. Demographic data, clinical and laboratory findings, comorbidities and treatments were collected and analyzed. Results: Among 86 patients with confirmed COVID-19, 54 patients (62.8%) were male, and the mean (SD) age was 66.6 (11.1) years. Overall, 65% patients presented with at least one neurological symptom. Twenty patients (23.3%) had symptoms involving the central nervous system, including delirium, cerebrovascular diseases and hypoxic-ischemic brain injury, while 6 patients (7%) had neuromuscular involvement. Seven of 86 patients exhibited new stroke and 6 (7%) cases were ischemic. A significantly higher prevalence of antiphospholipid antibodies was observed in patients with ischemic stroke than in those without stroke (83.3% vs 26.9%, p<0.05). Patients with ischemic stroke were more likely to have a higher myoglobulin level, and a lower hemoglobin level. Conclusions: The clinical spectrum of neurological complications in critically ill patients with COVID-19 was broad. Stroke, delirium and neuromuscular diseases are common neurological complications of COVID-19. Physicians should pay close attention to neurological complications in critically ill patients with COVID-19.